2023
DOI: 10.58314/ehi766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Entrepreneurship Education on Social Startup Creation: A Study of Selected Public Universities

Ejos Mercy OGBARI,
Preye Samson INGOMOWEI

Abstract: Businesses fail due to lack of proper financial management practices. A lot of countries are in great recession because of mismanagement of public finance. Most developing nations have refused to implement good financial management practices in order to ensure transparency, and economic development in the country. However, the purpose of this research is to examine the relevance of financial management practices in developed and developing countries. In addition to the study, its aim is to compare how financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Thus, risk arises in investment evaluation because of the inability of financial managers to anticipate the occurrence of the possible future events with certainty and consequences cannot make any correct prediction about the cash flow sequence (Amusat et al, 2022;Blessing & Onoja, 2015). Ogbari et al (2023a) stressed that in a practical situation, it is necessary to incorporate risk and uncertainty in decision making analysis. The authors argued further that risk is applied to a situation where there are several possible outcomes and they are relevant as data to enable statistical evidence to be produced for predicting the possible outcome.…”
Section: Investment Appraisal Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, risk arises in investment evaluation because of the inability of financial managers to anticipate the occurrence of the possible future events with certainty and consequences cannot make any correct prediction about the cash flow sequence (Amusat et al, 2022;Blessing & Onoja, 2015). Ogbari et al (2023a) stressed that in a practical situation, it is necessary to incorporate risk and uncertainty in decision making analysis. The authors argued further that risk is applied to a situation where there are several possible outcomes and they are relevant as data to enable statistical evidence to be produced for predicting the possible outcome.…”
Section: Investment Appraisal Techniquesmentioning
confidence: 99%
“…The likelihood that an event will occur is known as probability and this is normally expressed in decimal form with of value between 'O' and I.A value of 'O' denotes a nil likelihood of occurrence, whereas a value of 'I' signifies absolute certainty. The total of the probabilities for events, which can possibly occur, must add to I.O.A probability of 0.4 means that event is expected to occur four times out of ten (Ogbari et al, 2023a;Olasehinde, 2020). The expected value (sometimes called expected ay off) is the weighted arithmetic mean of possible outcomes.…”
Section: Investment Appraisal Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches has shown that the advancements in the levels of technology in recent times has resulted to increase in social networking which has led to positive implications for most businesses across globally (Ogbari et al, 2023a;Ogbari et al, 2023b;Egounleti, 2022). Customers have access to timely information as they can quickly get it on the websites (Oracle, 2013).…”
Section: Digital Customer Journeymentioning
confidence: 99%
“…In addition, these technologies also provide increased and improved Analytics for these businesses. Some of the notable applications that can be combined with the current technologies to improve the above benefits are the mobile couponing and offering in-store assistance to their customers (Ogbari et al, 2023a;Ogbari et al, 2023b;Egounleti, 2022).…”
Section: Business Value Of In-store Technologymentioning
confidence: 99%